Strength and abrasion performance of recycled aggregate based geopolymer concrete - Lakew, Asfaw Mekonnen; Al-Mashhadani, Mukhallad M.; Canpolat, Orhan (YILDIZ TECHNICAL UNIV, 2022)
This experimental work evaluated geopolymer concrete containing fly ash and slag by partial replacement of natural coarse aggregate (NCA) with recycled coarse aggregate (RCA) to manufacture environmental-friendly concrete. The proportion of recycled aggregates considered consists of 10%, 20%, 30%, and 40% of the total coarse aggregate amount. Also, a steel fiber ratio of 0.3% was utilized. The mechanical properties and abrasion resistance of fly ash/slag-based geopolymer concrete were then assessed. Majorly, the mechanical strength of the concrete samples decreased by the increase of RCA content. The geopolymer concrete with 40% RCA gave 28.3% lesser compressive strength and 24% lower splitting tensile strength than NCA concrete at one year. Also, the flexural strength of concrete specimens was reduced by 35% (from 5.34MPa to 3.5MPa) with the incorporation of 40% RCA. The incorporation of 30% RCA caused 23% and 22.6% reduction in compressive strength at 56 days and one year, respectively. The flexural and splitting tensile strength of the specimens was not significantly reduced (less than 10%) with the inclusion of a recycled coarse aggregate ratio of up to 30%. Furthermore, the abrasion wear thickness of every concrete sample was less than 1 mm. RCA inclusion of 20% produced either insignificant reduction or better strength results compared to reference mixtures. As a result, it was considered that the combination of 0.3% steel fiber and 20% recycled coarse aggregate in fly ash/slag-based geopolymer concrete leads to an eco-friendly concrete mix with acceptable short and long-term engineering properties that would lead to sustainability in concrete production and utilization sector.
Keywords: Compressive strength; splitting tensile strength; Fexural strength; Abrasion resistance; Geopolymer concrete; Recycled aggregate; Engineering